Attention to audiovisual speech does not facilitate language acquisition in infants with familial history of autism. (4th March 2022) - Chawarska, Katarzyna; Lewkowicz, David; Feiner, Hannah; Macari, Suzanne; Vernetti, Angelina
Abstract : Background: Due to familial liability, siblings of children with ASD exhibit elevated risk for language delays. The processes contributing to language delays in this population remain unclear. Methods: Considering well‐established links between attention to dynamic audiovisual cues inherent in a speaker's face and speech processing, we investigated if attention to a speaker's face and mouth differs in 12‐month‐old infants at high familial risk for ASD but without ASD diagnosis (hr‐sib; n  = 91) and in infants at low familial risk (lr‐sib; n  = 62) for ASD and whether attention at 12 months predicts language outcomes at 18 months. Results: At 12 months, hr‐sib and lr‐sib infants did not differ in attention to face ( p = .14), mouth preference ( p = .30), or in receptive and expressive language scores ( p = .36, p = .33). At 18 months, the hr‐sib infants had lower receptive ( p = .01) but not expressive ( p = .84) language scores than the lr‐sib infants. In the lr‐sib infants, greater attention to the face ( p = .022) and a mouth preference ( p = .025) contributed to better language outcomes at 18 months. In the hr‐sib infants, neither attention to the face nor a mouth preference was associated with language outcomes at 18 months. Conclusions: Unlike low‐risk infants, high‐risk infants do not appear to benefit from audiovisual prosodic and speech cues in the service of language acquisition despite intact attention to these cues. We propose that impaired processing of audiovisual cues may constitute the link between genetic risk factors and poor language outcomes observed across the autism risk spectrum and may represent a promising endophenotype in autism.